Devolution in Pakistan : An Assessment and Recommendations for Action - World Bank (Washington, DC, 2013)
The Devolved Service Delivery Study (DSD) is the product of an agreement between the World Bank, the Asian Development Bank, and the Department for International Development (the United Kingdom), in response to a request from the Government of Pakistan that the agencies review progress toward improving service delivery through decentralization. Pakistan's far-reaching devolution initiative has been designed with three broad and inter-related objectives in mind: To inject new blood into a political system considered to be the domain of historically entrenched interests; to provide positive measures enabling marginalized citizens--women, workers, peasants-to access formal politics; and to introduce a measure of stability into a turbulent political scene by creating a stronger line of accountability between new politicians and local electorates. Underpinning the political strategy were other technical objectives: improved delivery of social services; better determination and enforcement of property and labor rights and regulation of economic activities; and access to justice in the form of improved performance by local administrations, courts and police, with greater awareness of basic human rights protected under devolution. Based on an empirical study of 6 districts and 12 municipalities (Tehsil Municipal Administrations) (TMAs), this paper evaluates the extent to which the new structure has succeeded in creating the incentives necessary for local governments to achieve at least some of the service delivery objectives. This report notes that remarkable progress has been achieved. New local institutions with new structures for local government, new arrangements for intergovernmental sharing of resources, new electoral arrangements, new rules for government formation and dismissal and new opportunities for citizens to participate in the affairs of government have all been created. At the same time as the devolution initiative was being implemented, the government also implemented significant reforms in tax, trade, deregulation and privatization, the banking sector, anticorruption, restructuring federal and provincial legislatures and responding to gender concerns.